109k views
0 votes
What is the first step to solving this
equation?
4(2x-3)=4

2 Answers

4 votes

Answer:

x=2

Explanation:

Let's solve your equation step-by-step.

4(2x−3)=4

Step 1: Simplify both sides of the equation.

4(2x−3)=4

(4)(2x)+(4)(−3)=4(Distribute)

8x+−12=4

8x−12=4

Step 2: Add 12 to both sides.

8x−12+12=4+12

8x=16

Step 3: Divide both sides by 8.

8x /8 = 16 /8

x=2

User Yousf
by
4.4k points
4 votes

Answer:

x = 2

Explanation:

4(2x-3) = 4

4 × (2x-3) = 4 × 1

(2x-3) = 1 (divide both sides by 4)

2x = 1 + 3 (Move 3 to the right hand side)

2x = 4

x = 4/2

x = 2

User MrClean
by
4.9k points